Strontium and Neodymium Isotopic Signatures in Basalt Glasses of the Mid-Atlantic Ridge, 12°–31° N - Tskhovrebova, A. R.; Shabykova, V. V.; Silantyev, S. A.; Buikin, A. I. (Geochemistry international, 2023)
This paper presents the new geochemical isotope (Sr–Nd system, H 2 O, Cl) data obtained for basalt glasses of the Mid-Atlantic Ridge (MAR) sampled from six areas of the MAR axial zone between 31° and 12° N. The data are consistent with the existing ideas about large-scale geochemical segmentation of the MAR. It is shown that samples from predominantly serpentinite segments have a narrower range of variations of strontium isotopic composition ( 87 Sr/ 86 Sr = 0.7027–0.7032) in comparison with samples collected from the areas where the crustal section is dominated by basalts ( 87 Sr/ 86 Sr = 0.7024–0.7041). The variation ranges of the neodymium isotopic composition in these two groups of samples are almost identical (εNd = +4.9 to +10.9 and +5.9 to +11.6 in serpentinite and basalt segments, respectively), although, in general, serpentinite segments have a slightly more enriched composition. The wide variations of the neodymium isotopic composition and increased contents of Cl, H 2 O, and U, as well as increased K 2 O/TiO 2 and La/Sm ratios, in samples from serpentinites can most probably be related to the participation of different geochemically heterogeneous sources in the magmatism of the MAR axial zone. The influence of enriched plume-type matter cannot be excluded in some segments. The isotopic composition of noble gases may shed light on the subject.